THE IMPACT OF SHORT-TERM AND LONG-TERM FINANCING STRUCTURES ON PROFITABILITY AT PT PAKUWON JATI TBK - Marcella, Angela Celine; Putriani, Made Thalia; Kamaliah, Adisti (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This study examines the effect of short-term and long-term financing on the profitability of PT Pakuwon Jati Tbk during the 2020–2024 period using a quantitative associative-verificative approach. The research utilizes time series data obtained from the company’s annual financial reports, which were analyzed through multiple linear regression methods. The results show that short-term financing has a coefficient value of 2.530 with a p-value of 0.332, which exceeds the significance level of 0.05, while long-term financing has a coefficient of -1.419 with a p-value of 0.340, also above 0.05. These findings indicate that both short-term and long-term financing have no significant effect on the company’s profitability. The absence of influence suggests that the company’s management strategy places greater emphasis on maintaining liquidity stability rather than relying heavily on debt to increase profits. Additionally, the company’s profitability is influenced more by internal and external factors such as project diversification, operational efficiency, and prevailing market conditions. This implies that financing decisions alone are not the main determinant of profitability performance. Therefore, PT Pakuwon Jati Tbk is encouraged to continuously evaluate the efficiency of debt utilization and adopt a more holistic financial management strategy that integrates financing structure, asset management, and market responsiveness to achieve sustainable profitability growth in the future.